Biografi Abu Yusuf Biografi Abu Yusuf dan Kontribusinya dalam Pemikiran Ekonomi Islam: .. - baiti, nur (Maliki Interdisciplinary Journal, 2025)
Abu Yusuf (731–798 AD) was one of the important figures in Islamic economic thought. He is known as the main student of Imam Abu Hanifah and the author of the Buku al-Kharaj which discusses the principles of taxation and fiscal administration in Islam. His thinking emphasizes the importance of justice in the economic system, especially in the management of taxes and public finances. He proposed that taxes be collected fairly without burdening the people and should be used for infrastructure development and social welfare. Apart from that, Abu Yusuf also highlighted the active role of the state in maintaining economic stability and preventing detrimental economic practices, such as monopoly and exploitation. His intellectual contributions in the fields of taxation, state financial administration systems, and sharia-based economic policies are still relevant today. Through his rational approach, Abu Yusuf succeeded in developing the qiyas and istihsan methods in establishing Islamic economic law, which allows flexibility in its application in various social contexts. His thinking has had a major influence on the modern Islamic economic system and remains the main reference in Islamic economic studies